Proceedings of the 3rd International Conference on Material, Mechanical and Manufacturing Engineering 2015
DOI: 10.2991/ic3me-15.2015.310
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on the Impact of Lubricating Oils on Engine Friction and Vehicle Fuel Economy

Abstract: Keywords: energy-conserving engine oil; low viscosity; friction modifier; viscosity index improver; engine friction; vehicle fuel economy Abstract. The engine friction loss and vehicle fuel economy aiming at several kinds of energy-conserving engine oils with different quality standard, viscosity grade, friction modifier, and viscosity index improver were tested in this paper. Experimental results showed that the engine friction loss was reduced and vehicle fuel economy was improved by lowering the viscosity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In this study, the improvement of the fuel efficiency of ULV engine oils was calculated from the correlation between the KV100 of 5W-30 to 0W-16 engine oil and the rate of improvement of the fuel efficiency based on the values reported by Mo et al [21], Fujimoto et al [22], Kaneko et al [23], and Liu et al [24], as shown in Figure 4. Compared with conventional 0W-16 engine oil (KV100 6.2 mm 2 /s), the rates of improvement of the vehicle fuel economy of ULV-Mineral and ULV-PAO were estimated to be 0.6 and 1.1%, respectively.…”
Section: Results Of Analysis For Improving the Fuel Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the improvement of the fuel efficiency of ULV engine oils was calculated from the correlation between the KV100 of 5W-30 to 0W-16 engine oil and the rate of improvement of the fuel efficiency based on the values reported by Mo et al [21], Fujimoto et al [22], Kaneko et al [23], and Liu et al [24], as shown in Figure 4. Compared with conventional 0W-16 engine oil (KV100 6.2 mm 2 /s), the rates of improvement of the vehicle fuel economy of ULV-Mineral and ULV-PAO were estimated to be 0.6 and 1.1%, respectively.…”
Section: Results Of Analysis For Improving the Fuel Efficiencymentioning
confidence: 99%
“…It has been shown that engine torque loss decreases as the viscosity decreases until the kinematic viscosity was 4.2 mm 2 /s at 100 °C (KV100), whereas a decrease of the viscosity below 4.2 mm 2 /s causes an increase in engine torque loss [25]. In this study, the improvement of the fuel efficiency of ULV engine oils was calculated from the correlation between KV100 and fuel efficiency using the results of the above-mentioned literatures [21][22][23][24], as our previous research has demonstrated [26]. A certain correlation has been confirmed with KV100 and high temperature high shear (HTHS) viscosity [27], which has been known to linearly correlate with the fuel economy in NEDC mode [28], and it is reliable to calculate the improvement of the fuel efficiency of ULV engine oils by using KV100.…”
Section: The Methods Of Analyzing the Effect Of Improving Fuel Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, fuel economy enlightens the automobile efficiency of consumption in petroleum products and is expected to have a substantial impact in reducing adverse environmental effects [14,15]. Additionally, at the individual and firm level, the focus on fuel economy is also likely to create substantial benefits in terms of the expected reduction in vehicle operating costs [16,17]. A critical aspect in the attainment of fuel economy has been considered to evaluate the performance of the factors that influence automobile fuel consumption.…”
Section: Introductionmentioning
confidence: 99%